Viral factories in rotavirus-infected cells: interactions between protein and RNA components - Patton, John T (Future virology, 2007)
Rotavirus infection leads to the formation of large electron-dense inclusion bodies within the cytoplasm. These inclusions, termed viroplasms, represent viral factories in which the segmented double-stranded RNA genome of rotavirus is replicated and packaged into virion precursors. The two essential building blocks of the viroplasm are the nonstructural protein (NSP)2 octamer, a doughnut-shaped structure with RNA-binding and nucleoside-triphosphatase activities and dimers of the NSP5 phosphoprotein. Through the use of single-particle cryoelectron microscopy and 3D reconstruction, Jiang and colleagues obtained subnanometer images revealing that the two ligands, NSP5 and RNA, competitively bind to deep grooves spanning the surface of the NSP2 octamer. These results represent a major breakthrough in our understanding of the macromolecular interactions involved in the assembly and function of viral factories.